Effect of drying method on the antioxidant capacity of Cosmos Caudatus extract - Shazwani , Ibrahim (2013)
Cosmos caudatus have high an ioxidant capacity and able to contribute to the capability to scavenge free radical ions and reduce oxidative stress. However, the antioxidants may decrease during the drying process which further reduces the functionality of the herb. The purpose of this study was to investigate the effect of drying methods on the antioxidant capacity of C. caudatus extract. Three different types of drying treatment were set; freeze dryer (-40°C, 72 hours), spray dryer (150°C, 20 rpm of pump setting, 50 rpm of fan setting) and oven dryer (40°C, 72 hours). In this study, Soxhiet extraction method was used and distilled water and 70% acetone (v/v) as the extraction solvent. The determination of antioxidant and ascorbic acid content were tested by DPPH assay and HPLC analysis respectively. Freeze-dried sample of 70% acetone (v/v) exhibits highest concentration of antioxidant (59.00 mgAAE/g) followed by spray-dried and oven-dried sample (37.00 mgAAE/g and 36.00 mgAAE/g) respectively. HPLC analysis shows significant results of ascorbic acid content where freeze-dried sample of 70% acetone (v/v) exhibits highest ascorbic acid concentration followed by spray-dried and oven-dried samples (1.09 mgAAE/g, 0.69 mgAAE/g and 0.48 mgAAE/g) respectively. Freeze dryer was the efficient technique for the preservation of antioxidant compounds followed by spray dryer and oven dryer. Further study is proposed by differentiating predrying temperature and drying periods used for each dryer to discover the effect of predrying temperature and drying period on the antioxidant compounds preserved.